Two new metazoans from the Cambrian Guanshan biota of China - Zhao, Jun; Li, Yujing; Selden, Paul A. (Frontiers in Ecology and Evolution, 2023)
Here, we describe two new sessile epibenthic metazoans that show character traits with cnidarians and bryozoans. If confirmed, the new material can help to understand the origin and early evolution of these two phyla. The discovery of more sessile epibenthos suggests that the benthic ecosystem of the Guanshan biota (Cambrian Series 2, Stage 4) is more diverse than previously thought.